Benefits and harms of direct to consumer advertising: a systematic review. Issue 4 (1st August 2005) - Gilbody, S; Wilson, P; Watt, I
Abstract : Background: Direct to consumer advertising is increasingly used by the pharmaceutical industry, but its benefits and harms have yet to be summarised in a comprehensive and rigorous manner. Methods: A systematic review was conducted of robust evaluations of the impact (positive and negative) of direct to consumer advertising. A broad range of databases and data sources (including Cinahl, Embase, HMIC, HSRProj, Medline, PsycInfo, and the internet) were searched from inception to 2004. Results: From 2853 citations only four reports were found that met the strict inclusion criteria and provided usable results. Direct to consumer advertising is associated with increased prescription of advertised products and there is substantial impact on patients' request for specific drugs and physicians' confidence in prescribing. No additional benefits in terms of health outcomes were demonstrated. Discussion: Direct to consumer advertising is banned in most countries, and the research evidence tends to support the negative impact that is feared by those who support a legislative ban. Further research is needed into the clinical and economic impact of direct to consumer advertising in healthcare systems.